The Nazis : a warning from history. Volume 3 (United Kingdom : BBC Worldwide, 2004)
Contents: The road to Treblinka--Fighting to the end.
"2 Titles in each DVD"--Cover.
Keywords: International Baccalaureate; World War II; Film (Documentary).; Documentary films